PENGEMBANGAN MODEL PEMBELAJARAN PROJECT BASED LEARNING DALAM PEMBELAJARAN MENULIS BERITA - Wismanto, Agus (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This development research aims to produce a project-based learning model product in learning to news writing. This research procedure follows the Borg & Gall development procedure. The research subjects were students and lecturers of the PBSI study program at Universityof PGRI Semarang. This development process produces products in the form of producing project-based learning model products in learning to news writing that are valid, practical and effective. This study uses a non-test instrument data collection technique, namely a questionnaire given to 2 material experts and 2 media experts. The results of the feasibility of the product producing a project based learning learning model product in learning to news writing using a Likert scale in the form of a score of 1-5 are as follows: a) The results of validation by material experts obtained a score of 81.54% which is included in the very feasible category; b) The results of the validation by media experts obtained a score of 78.4% which was included in the appropriate category. Based on the results of the feasibility, it can be concluded that the product of the project based learning model is suitable for use in learning to news writing